Case report: Cardiac neuroendocrine carcinoma and squamous cell carcinoma treated with MR-guided adaptive stereotactic radiation therapy - Chen, Xinru; Weng, Julius K.; Sobremonte, Angela; Lee, Belinda M.; Hughes, Neil W.; Mohammedsaid, Mustefa; Zhao, Yao; Wang, Xiaochun; Zhang, Xiaodong; Niedzielski, Joshua S.; Shete, Sanjay S.; Court, Laurence E.; et al. (Frontiers in Oncology, 2024)
We present two cases of cardiac metastases adjacent to the right ventricle in a 55-year-old male and a 61-year-old female, both treated with magnetic resonance (MR)-guided adaptive stereotactic radiation therapy (SBRT). The prescribed regimen was 30Gy delivered in 3 fractions using a 1.5 Tesla magnetic resonance linear accelerator (MR-linac). Patients exhibited favorable tolerance to the treatment, with no observed acute toxicity.